The reflective approach in pre-service foreign language teacher education - Mardešić, Sandra (Array, 2013)
Contemporary research in pre-service teacher education is oriented towards the development of teaching competences through the reflective approach and experiential learning. In the context of changes in teacher education within the 'Bologna reform process', Croatian universities have applied a competence-developing model, introducing more teaching-oriented courses in various fields, such as psychology, pedagogy, and those more specific to foreign languages, second language acquisition, glotodidactics, evaluation and testing etc., for a total 60 ECTS, as well as more hours of teaching practice in schools. However, since previous research showed that pre-service teachers have difficulties in linking theory and practice, the reflective approach has been recently tested by applying a new instrument, the European Portfolio for Student Teachers of Languages together with reflective essays. The examination of the structure of teacher competences through students' self- assessment using descriptors in the portfolio showed that the new curriculum develops well some categories of competences, lesson planning, using resources and conducting a lesson. However it also shows the need for further improvement in certain aspects of student teachers’ knowledge: teaching reading and writing skills, learning strategies and styles, and above all, evaluation and testing of pupils’ knowledge, which does not seem to be sufficiently developed. The application of a portfolio as a form of formative assessment of professional growth has shown a positive effect in the projected goal of stimulating reflection on one’s own work in the classroom and on raising awareness of the need for further development of certain aspects of teaching as a lifelong process. It has also proved to be a useful method for linking theoretical and practical knowledge, thus creating a ground for potentially more efficient foreign language teacher education. Reflective essays also showed to be a useful method of stimulating student’s reflection on their teaching knowledge and setting goals for future learning. Therefore, we can conclude that applying this approach to teacher education could significantly contribute to the improved quality of initial teacher training of future foreign language teachers. Based on the overall results, we have constructed a new theoretical model of acquisition of teachers’ competences by application of the reflective approach, suitable for Croatian educational context. The model includes three types of reflection: reflection for action, reflection in action, and reflection of action.